2020
DOI: 10.1136/bmjopen-2019-032332
|View full text |Cite
|
Sign up to set email alerts
|

International mixed methods study protocol to develop a patient-reported outcome measure for all types of chronic wounds (the WOUND-Q)

Abstract: IntroductionMost patient-reported outcome measures (PROM) for chronic wounds are specific to a single wound type (eg, pressure ulcer) or part of the body. A barrier to outcome assessment in wound care and research is the lack of a rigorously designed PROM that can be used across wound types and locations. This mixed method study describes the protocol for an international collaboration to develop and validate a new PROM called the WOUND-Q for adults with chronic wounds.Methods and analysisIn phase I, the quali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…We previously published a protocol paper that described our approach to develop the WOUND‐Q. 25 Our multi‐phase mixed methods approach adheres to published guidelines for the development and translation of a PROM. 26 , 27 , 28 , 29 , 30 In phase 1 (qualitative), an interpretive description qualitative approach was followed, which built on existing clinical and research knowledge.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We previously published a protocol paper that described our approach to develop the WOUND‐Q. 25 Our multi‐phase mixed methods approach adheres to published guidelines for the development and translation of a PROM. 26 , 27 , 28 , 29 , 30 In phase 1 (qualitative), an interpretive description qualitative approach was followed, which built on existing clinical and research knowledge.…”
Section: Methodsmentioning
confidence: 99%
“…We previously published our interview guide. 25 The guide included open‐ended questions that aimed to elicit concepts of interest from patients about outcomes (eg, physical, psychological, and social life) and experiences (eg, information and wound care team) of wound care. As interviews progressed and participants discussed topics not on the interview guide, the guide was revised to include these new concepts for probing in subsequent interviews.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The data used for this study were collected as part of a larger phase I qualitative study to understand patient‐reported quality of life outcomes and health care experiences among patients with chronic wounds (WOUND‐Q) 41 . Results of our quality of life outcomes study have been reported separately 41 . The objective of the current study was to describe patient‐reported experiences and health care processes that impact quality of care for chronic wounds.…”
Section: Methodsmentioning
confidence: 99%
“…For this study, we used an interpretive description approach, which aims to generate knowledge relevant for a clinical context by building on existing theoretical knowledge, clinical knowledge, and a scientific basis to inform a study 43 . Four experienced qualitative researchers performed semi‐structured interviews in the native language of each patient using a common interview guide (Appendix A) 41 . For patient convenience, interviews were conducted in‐person or by telephone.…”
Section: Methodsmentioning
confidence: 99%